Tak Nak (Say No) anti-smoking television advertisement: is it influential enough to stop smoking? - Zawawi, Dahlia; Chew, Jong Dick (Universiti Putra Malaysia Press, 2013)
This paper aims to look at the levels of exposure, awareness, receptivity, and assessment of the Tak Nak (Say No) anti-smoking television advertisement in Malaysia. At the same time, the study also explores possible relationships between the said factors with the intent to smoke. The study utilized self-administrated questionnaires to survey the perceptions people hold regarding the above stated matters. Despite the evidence showing the ineffectiveness of the Tak Nak anti-smoking television advertisement, the respondents still believe that all the elements (namely, exposure, awareness, receptivity, and assessment) are able to influence the intent to smoke. All the factors [exposure (χ2 = 14.151, ρ = 0.007), awareness (χ2 = 10.471, ρ = 0.033), receptivity (χ2 = 33.149, ρ = 0.000), and assessment (χ2 = 10.359, ρ = 0.035)] show significant relationships with the intent to smoke.